PVD Bond Coat

By using PVD technology to form a gradient layer structure on ultrachromium alloy materials, the problem of complex and high cost in the existing technology is solved, and efficient thermal and wear performance is achieved, and suitable for high-temperature oxidation and corrosion environments.

JP7671568B2Active Publication Date: 2025-05-02OERLIKON SURFACE SOLUTIONS AG PFAFFIKON
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2019556811
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-04-21
Filing Date
2018-04-19
Publication Date
2025-05-02
Estimated Expiration
2038-04-19

AI Technical Summary

Technical Problem

The prior art has limitations in improving the thermal and wear properties of ultrachrome alloy materials, especially in high temperature and oxidative corrosion environments. The existing coating technology is complex and costly, making it difficult to meet the performance requirements of next-generation engines.

Method used

Using physical vapor deposition (PVD) technology, a series of gradient layer structures are formed on the superchromium alloy matrix, including the interface layer (IF-1), the transition layer (TL) and the barrier layer (IF-2), and the oxygen content and metal composition of the layer are controlled by adjusting the oxygen partial pressure and the parameters of the arc light source, thereby improving the performance of the coating.

Benefits of technology

It realizes simplified coating process, reduces costs, improves the thermal and wear properties of ultra-chrome alloy materials, enhances oxidation and corrosion protection capabilities, and is suitable for high-temperature applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007671568000004
    Figure 0007671568000004
  • Figure 0007671568000005
    Figure 0007671568000005
  • Figure 0007671568000006
    Figure 0007671568000006
Patent Text Reader

Abstract

1. A superalloy workpiece comprising: a superalloy substrate; an interface layer (IF-1) of essentially the same superalloy composition directly on a surface of the superalloy substrate; followed by a transition layer (TL) of essentially the same superalloy and superalloy oxide or a different metal composition and different metal oxide, wherein the oxygen content of the transition layer is increased from IF-1; and a barrier layer (IF-2) of superalloy oxide or a different metal oxide.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of coated superalloy (SA) materials, in particular to a coating method according to claim 1, to a workpiece according to claim 12 and to a method for manufacturing a workpiece according to claim 26. [Background technology]

[0002] Superalloys exhibit several important properties such as excellent mechanical strength, resistance to thermal creep deformation, good surface stability and corrosion or oxidation resistance. The crystal structure is usually face-centered cubic austenitic. Examples of such alloys are Hastelloy, Inconel, Waspaloy, Rene alloys, Haynes alloys, Incoloy, MP98T, TMS alloys and CMSX single crystal alloys. Superalloys derive their high temperature strength from solid solution strengthening. The important strengthening mechanism is precipitation strengthening, which is the formation of secondary phase precipitates such as gamma prime and carbides. Oxidation or corrosion resistance is provided by elements such as aluminum and chromium. Basically, there are two types of superalloys, the Co-based superalloys with cobalt as the main metallic component, e.g., C, Cr, W, Ni, Ti, Al, Ir, and Ta as alloying elements, and the Ni-based superalloys, which are the most important class to date, with nickel as the main metallic component, e.g., Cr, Fe, Co, Mo, W, Ta, Al, Ti, Zr, Nb, Re, Y, V, C, B, or Hf, being just a few examples of the alloying additions used in this group of superalloys. One focus of the present invention is to improve the thermal and wear properties of superalloys in general, and in particular for applications such as high and low pressure turbine components for aerospace and industrial gas turbine (IGT) applications, for which several successful experiments have been carried out with Ni-based superalloys such as PWA 1483 and CM 247-DS. Furthermore, aluminide-based alloys as TiAl-based superalloys such as γ-TiAl, or further aluminide-forming high temperature and high wear resistant alloys including Ni-aluminides as NiAl or NiAl3 also known as Raney Nickel, Fe-aluminides, Hf-aluminides, Cr-aluminides, Nb-aluminides such as Nb3Al or NbAl3, Ta-aluminides such as Ta3Al or TaAl3, Pt-aluminides, Zr-aluminides, etc. are understood herein as superalloy compositions.

[0003] Spark plasma sintering (SPS) is a powder metallurgical manufacturing method, whereby a powder composition is pressed in a graphite die, preferably between two graphite punches, for example under vacuum, and a DC current or optionally a pulsed DC current is applied simultaneously between the two punches to assist the shaping process of the workpiece to be manufactured, in this case the target. Thereby, the DC current or the pulsed DC current passes directly through the graphite die and the powder compact, in the case of conductive samples such as superalloys. Thus, the heat generation is generated internally, in contrast to conventional hot pressing, where the heat is provided by an external heating element. This allows the sintering process to be generally very fast (within a few minutes), since it allows near theoretical density to be reached at low sintering temperatures compared to conventional sintering techniques, and facilitates very high heating or cooling rates (up to 1000 K / min). The general speed of the process ensures that it is possible to densify nano-sized or nano-structured powders, while avoiding the coarsening associated with standard densification routes. By way of example, for such a procedure, a series of 3 millisecond DC current pulses of intensity up to 1500 A and low voltage of 25 V can be passed directly to the powder sample and the press tool.

[0004] Research into materials used in high temperature, oxidation and corrosion environments is a continuous endeavor for application in aircraft, gas turbines and combustion engines. Despite the differences in final different uses, designs and dimensions, the trends in these industries are towards the same goal: continuous improvement of engine efficiency to reduce fuel consumption as well as comply with stricter regulations on CO2 emissions. This means operating engines at higher temperatures, which in turn increases the need for more robust, stable and resistant substrates that operate in the harsh environments of the various sections of turbine engines. Even with the use of state-of-the-art materials such as superalloys and composites, coating technology cannot be avoided when improving the life of components by increasing their oxidation, wear, corrosion and corrosion resistance at high operating temperatures. Despite the fact that coating technologies introduced decades ago are well established and are continuously improved by the use of new processes as well as new coating materials, the coating systems manufactured on engine parts are becoming more and more complex. Thus, for example, problems of interaction between layers, methods of surface manufacture, heat treatment and diffusion are becoming more and more important. Moreover, the requirements of the next generation of engines are very challenging, since these existing technologies have their limitations and cannot provide the necessary properties. A typical coating system for gas turbines generally consists of several layers: a bond coat, a thermally grown oxide and a top ceramic layer. The bond coat used to protect the turbine against oxidation is usually produced by a diffusion process for PtAl, by electron beam physical vapor deposition (EB-PVD) for MCrAlY or by low pressure plasma spraying (LPPS). The bond coat PLANSEE and the top ceramic layer form the so-called thermal barrier coating (TBC). The top ceramic coating is produced by atmospheric plasma spraying (APS) as a porous coating or by EB-PVD as a columnar coating. The design of the bond coat is challenging since it has to realize two high-performance interfaces: one that guarantees mechanical stability over a wide temperature range for the superalloy substrate and the other that provides a good oxygen barrier for the porous oxide.This implies not only a rational design of the bond coat, but also a need for high reproducibility in the manufacture of the coating system (stack of layers). [Prior art documents] [Non-patent literature]

[0005] [Non-Patent Document 1] Journal of Applied Crystallography 42 (2009) 726-729 Summary of the Invention [Problem to be solved by the invention]

[0006] It is therefore an object of the present invention to improve and simplify known coating processes for superalloys by avoiding the drawbacks of state of the art methods, such as the use of expensive coating materials such as PtAl and the use of processes such as EB-PVD, which are complex and cumbersome when coatings composed of elements with different vapor pressures need to be applied. A further object of the present invention is to improve existing coatings, e.g. in terms of overall performance, in order to overcome limitations and inability of state of the art coating systems. [Means for solving the problem]

[0007] Therefore, the object of the present invention is to providing a superalloy (SA) substrate to a PVD coating unit; - providing a superalloy target as a cathode of an arc evaporation source of a coating unit; applying a substrate bias to the substrate; - depositing an interface layer (IF-1) of a superalloy on the surface of the substrate by vacuum arc deposition from a superalloy target; - providing a reactive gas supply comprising oxygen to the coating unit; - depositing by vacuum arc deposition a transition layer (TL) of the same superalloy or of a different metal composition, in which the oxygen content of the layer is changed from (IF-1) towards the surface by varying the partial pressure of the reactive gas in the process atmosphere, e.g. by increasing the oxygen content of the layer from (IF-1) towards the surface by increasing and / or varying the partial pressure of the reactive gas; - depositing, by vacuum arc deposition in a process atmosphere similar to that of the deposition of the transition layer (TL) but with a higher concentration of reactive gas, a barrier layer (IF-2) subsequent to the transition layer, which comprises a higher amount of superalloy oxide or a different metal oxide composition than in the transition layer; The present invention discloses a coating method comprising the steps of:

[0008] The variation of the oxygen content in the transition layer can be achieved by increasing / changing the flow of the oxygen-containing reactive gas in a step or ramp and / or by varying the power of the arc source. Typically, oxygen (O2) gas is used as the reactive gas, although any other volatile oxygen-containing compound such as ozone (O3) can also be used.

[0009] Such a coating process can be carried out by using a superalloy target having essentially the same composition as the superalloy. The powder composition for producing the target is thereby selected according to the composition of the superalloy to be coated, producing a target of essentially the same composition as the superalloy itself. Essentially the same composition in this case with respect to the target means that, when produced by SPS or other powder metallurgy methods, the main elements constituting more than about 9% by weight of the powder mixture, such as Ni, Co, Cr for example in PWA1483, differ by no more than ±20%, preferably no more than ±10%, when produced by SPS or other powder metallurgy methods, due to the effects of production and / or, for example, EDX measurements. The same applies to targets used in reactive or non-reactive processes, whereby the difference from the original powder composition may be slightly larger for a single main component. The same applies to the meaning of the term essentially the same composition as the composition of the interface layer (IF-1). Ni-, Al-, C-, Co-, Cr-, Mo-, Ta-, Ti- and W powders were used, among others, to produce the targets for cathodic vacuum arc coating described below.

[0010] Alternatively, the superalloy solid can be milled to produce a suitable powder which can then be used to form a target by SPS or another powder metallurgy process.

[0011] In the most basic process, the same superalloy target is used to deposit all layers of the bond coat, and oxygen is used as the only process gas.

[0012] Furthermore, in terms of process stability, e.g. low formation of droplets, construction of a perfectly matched IF-1 layer, it proves beneficial to provide targets with mainly the same crystal structure, e.g. with regard to crystallographic coherence and epitaxy onto the substrate, which in the case of Ni or Co-based superalloys means about 80-99% fcc crystal target structure.

[0013] In a further embodiment of the invention, at least one further target with a further metal composition is provided for depositing a transition layer of a different metal composition and / or a barrier layer of a different metal oxide composition (IF-2). This can be done by providing an additional elemental or composite target to the coating unit. This can be done either by co-arcing with the superalloy target and / or by stand-alone arcing of at least one target of a further metal composition, whereby a transition phase using both types of targets for depositing the respective coating is preferred. The composition of the target of the further metal composition is thereby selected such that a layer of a different metal composition and / or a different metal oxide composition can be deposited from the target of the further metal composition alone or by co-arcing with the superalloy target.

[0014] Alternatively, or in combination with the use of targets of the aforementioned additional metal composition, a gaseous precursor containing the additional metal to be deposited can be introduced into the PVD coating unit in parallel with the vacuum arc deposition of the superalloy target to deposit a transition layer of a different metal composition and / or a barrier layer of a different metal oxide composition (IF-2). Such precursors can be introduced into the coating apparatus using the inert or reactive gas supply lines or in a separate line.

[0015] It should be noted that despite the fact that the ratios of the major metal components at least in the transition layer and in IF-2 are generally similar, the ratios of any metals can be varied stepwise or ramped between or even within each layer, for example by simultaneously arcing two or more targets of different metal composition and varying the respective power input of one or both targets, or by varying the flow rate of one or more gaseous precursors, or by applying a combination of each of the aforementioned methods. Such variations in metal content are particularly applicable when forming oxides with oxidation barrier properties, which are standard TBC designs formed by high temperature oxidation of high aluminum content surfaces prior to the deposition of a porous oxide. One of the goals of the new PVD bond coat designs described herein is to replace high temperature oxidation with oxide formation in a PVD in situ process.

[0016] In a further embodiment of the invention, the interface layer (IF-1) is deposited with a crystal structure that is compatible with that of the superalloy substrate, whereby even an epitaxially grown structure could be deposited that reflects the crystal structure of the respective surface location of the superalloy SA. Such a compatible, and in particular epitaxially grown, crystal structure, imparted to a polycrystalline, directionally solidified (DS) or single crystal (SX) SA surface, has been shown to provide superior properties of the overall coating in terms of oxidation resistance and adhesion.

[0017] Preferably, the superalloy oxides and / or oxides of different metal compositions of the barrier layer (IF-2) are deposited in an oxygen excess in a reactive gas atmosphere. The ratio of oxygen atoms to metal atoms (=excess) may be at least 1.5, or even at least 5, in order to form thermodynamically stable oxides, in particular the most stable oxides, from the superalloy metals and / or different metal compositions evaporated during the deposition of the barrier layer (IF-2). This allows the formation of a barrier layer that comprises essentially stoichiometric oxides in the thermodynamically most stable phase for most or all metal elements and / or superalloys or alloys of different metal compositions. Such a barrier layer (IF-2) exhibits a dense columnar structure that is very different from the polycrystalline structure with almost random grain orientation of the interface layer (IF-1) deposited on the surface of a polycrystalline SA, for example.

[0018] In contrast to the barrier layer, the interface layer can be deposited with pure metal vapor without process gas, or an inert gas supply can be provided to the coating unit to deposit at least one of the interface layer (IF-1), transition layer and barrier layer (IF-2) in an inert gas-containing process atmosphere.

[0019] Regarding important coating parameters such as process pressure, arc current and substrate bias, the following should be noted.

[0020] The process pressure range used for the deposition of the interface (IF-1) was 0.1 mPa - 100 mPa without the use of inert gas. With the addition of inert gas the pressure increased to about 0.1 Pa - 5 Pa. Further process parameters for the interface layer were as follows: Arc current for superalloys: 80A~250A, Substrate bias: -20V~-800VDC and bipolar pulse bias.

[0021] The process pressure range used for depositing the transition layer (TL) in oxygen reactive gas was 0.1 Pa - 5 Pa with or without the addition of inert gas. Typically the process pressure during the deposition of the transition layer was increased from the very low process pressure without reactive gas used for the deposition of the interface (IF-1, see above) to the process pressure for depositing the barrier layer (IF-2) with a large amount of reactive gas (see below). Further process parameters of the transition layer were as follows: Arc current for superalloys: 80A~200A, Arc current targeting further metal compositions: 60A-200A; Substrate bias: -20V to -800DC, and unipolar and bipolar pulses.

[0022] The process pressure range used for the deposition of the barrier layer (IF-2) was 0.1 Pa - 8 Pa without the use of inert gas. With the addition of inert gas the pressure increased to about 0.2 Pa - 10 Pa. Further process parameters for the interface layer were as follows: Arc current targeting superalloy: 60A~200A; Arc current targeting further metal compositions: 60A-220A; Substrate bias: -20V to -600VDC, preferably unipolar or bipolar pulse.

[0023] The composition of the target of the further metal composition is selected such that a layer of a different metal composition and / or a different metal oxide composition can be deposited from at least one target of the further metal composition alone or by co-arcing with at least one superalloy target. Alternatively or additionally, a precursor can be used that comprises at least one of the further metals to be deposited on the transition layer and / or barrier layer.

[0024] It has proven beneficial for the method to use superalloy targets manufactured by powder metallurgical processes, examples of such processes being hot pressing, hot isostatic pressing (HIP) and especially spark plasma sintering (SPS).

[0025] In a further embodiment of the present invention, in a further process step a further suitable porous ceramic top layer is applied to the surface of the barrier layer (IF-2).

[0026] Such top layers can be applied by thermal spraying techniques such as, for example, detonation spraying, wire arc spraying, flame spraying, high velocity oxy-fuel coating spraying (HVOF), high velocity air fuel (HVAF), hot water spraying, cold spraying, and preferably plasma spraying or vacuum plasma spraying.

[0027] The present invention also has the object of providing a method for producing a coated superalloy workpiece comprising the above-mentioned coating method. Such a workpiece may be, for example, any part used in the high temperature regions of an industrial gas turbine or an aircraft engine, such as turbine blades, vanes, etc.

[0028] A further object of the present invention is to -A superalloy substrate; - an interface layer (IF-1) of essentially the same superalloy composition directly on the surface of the superalloy substrate, followed by a transition layer (TL) of essentially the same superalloy and superalloy oxide, or a different metal composition and different metal oxide, the oxygen content of the transition layer being increased from IF-1; - a barrier layer of a superalloy oxide or a different metal oxide (IF-2), The present invention provides a superalloy workpiece comprising:

[0029] IF-1 can thereby have a crystal structure that is compatible, or even epitaxial, with the crystal structure of the surface of the superalloy substrate.

[0030] The oxygen content of the transition layer may increase stepwise or gradually from IF-1 to IF-2.

[0031] The different metal compositions in the transition layer may differ from essentially the same superalloy composition by at least one additional element.Similarly, the metal compositions of the different metal oxides of the barrier layer may differ by at least one additional metal present in the oxide form.

[0032] The at least one further element may have an electronegativity of 1.4 or less according to Pauling. Such a low electronegativity is usually the case for metals that have a high probability of combining with oxygen, for example when such metals are dispersed in a matrix of a solid metal with a low tendency to form oxides. Such a further element may be at least one of the lanthanides, preferably La, Er, or Yb. Alternatively, the different metal composition may differ from the superalloy composition in the concentration of at least one element or in the concentration and / or addition of at least one of the following further elements: Mg, Al, Cr, Er, Y, Zr, La, Hf, Si.

[0033] At least a portion of the further element may be oxidized and deposited within the grains as a solid solution (SS) and / or along the grain boundaries of the transition layer (TL) and / or barrier layer (IF-2) as a dispersion strengthening oxide (ODS).

[0034] It is known that metals with low electronegativity, such as alkali metals, alkaline earth metals, lanthanides, actinides, and some metals of groups 3 and 4 (transition metals) of the periodic table of elements, tend to form solid solutions (SS) within the grains of the solid main matrix, or to form oxide dispersion strengthened (ODS) solids, if such metals are located along the grain boundaries of a polycrystalline solid and are oxidized by the diffusion of oxygen atoms. The use of such thermodynamically stable materials (SS and / or ODS) is known to strengthen such alloys, for example superalloys, from the oxide dispersion hardening process, by adding only small amounts of oxide-forming elements (about 2% by volume). However, it is the first time that a similar effect has been demonstrated in a coating, when a coating according to the invention is deposited. It has been possible to show the effect of SS and / or ODS strengthening by partially oxidized superalloys in the transition layer.

[0035] The concentration of at least one of the metallic element and silicon in the transition layer may be adjusted or increased stepwise or gradually from IF-1 to IF-2.

[0036] The different metal oxides are the following oxides: Aluminum oxide, aluminum-chromium oxide, erbium oxide, yttrium oxide, yttrium-aluminum oxide, magnesium-aluminum oxide, aluminum-silicon oxide, hafnium-silicon oxide The composition may comprise at least one of the following or a mixture thereof:

[0037] Thereby, the aluminum oxide or aluminum-chromium oxide may be Al2O3 or (AlCr)2O3 comprising a corundum crystal structure, the erbium oxide or yttrium oxide may be Er2O3 or Y2O3 comprising a cubic crystal structure, and more than 55%, preferably more than 75%, of the respective crystal structure may be the respective corundum or cubic crystal structure.

[0038] The different metal oxides may include aluminum-containing oxides and the TL and / or IF-2 layers may include aluminum droplets or droplets with a high content of metallic aluminum.

[0039] For example, in the case of an oxide comprising aluminium-chromium oxide, with a corundum structure and / or dispersed as SS or ODS in the transition and / or barrier layers, the layer may comprise droplets with a high content of metallic chromium.

[0040] As an example, for IGT and aeronautical applications, a ceramic top layer can be provided as a termination layer on the surface of the top barrier layer (IF-2) of the bond coat. Such a top layer can be made with a porous structure to better accommodate thermal expansion in high temperature applications.

[0041] Next -Interface layer (IF-1) -Transition Layer (TL) and -Barrier layer (IF-2) For a bond coat consisting of successive layers of Any of the following coating thicknesses can be selected: 1μm≦d bond ≦200μm Interface layer thickness (IF-1): 0.01μm≦d IF-1 ≦20μm Transition layer (TL) thickness: 0.1μm≦d TL ≦100μm Barrier layer (IF-2) thickness: 1μm≦d IF-2 ≦50μm

[0042] The thickness of the subsequent thermal sprayed ceramic top layer for aeronautical or IGT applications was selected to be between 10 μm and 3 mm, which showed excellent adhesion and wear resistance.

[0043] The present invention will be further described below with examples and drawings. It should be noted that any combination of the embodiments, modifications or examples of the present invention, even if not explicitly mentioned in the present specification or claims, is considered to be part of the present invention by those skilled in the art, unless they are immediately recognized as dysfunctional by those skilled in the art.

[0044] In the following the invention is explained in an exemplary manner with the aid of experimental details and figures. [Brief description of the drawings]

[0045] [Figure 1] FIG. 1 illustrates an example of a layer concept and bond coat. [Diagram 2] FIG. 1 shows XRD patterns of virgin and engineered targets. [Diagram 3] FIG. 1 shows a micrograph and EBSD of the SA-T surface. [Figure 4] This is a TEM image of the SA-T surface. [Diagram 5] FIG. 1 shows EDX mapping. [Figure 6] FIG. 1 shows bright field and dark field micrographs, line scans. [Figure 7] FIG. 3 shows an XRD similar to FIG. 2 on sapphire. [Figure 8] FIG. 14. Layer stack: STEM bright field, TKD, quality map. [Figure 9] FIG. 1 shows a TEM micrograph of the interface. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0046] In the present invention, the concept of layers depicted in Figure 1a is introduced. This approach is based on the formation of the following layers: a "substrate-same" interface layer (IF-1) on the bulk superalloy substrate (SA-S), followed by a transition layer (gradient layer) from IF-1 to a partially or fully oxidized coating, terminating in a second interface layer (herein also called barrier layer) (IF-2). This IF-2 can be an oxygen diffusion barrier and / or nucleation layer of a porous oxide, as utilized in the design of the TBC. IF-2 can also be a mixture of oxides formed during the oxidation of ODS coatings or superalloy vapors. The entire stack of layers is synthesized in one process under vacuum conditions typical of physical vapor deposition (PVD). Non-reactive and reactive arc evaporation are utilized to generate this coating design by in situ processing.

[0047] An example of a basic bond coat on a polycrystalline superalloy is shown in FIG. 1b, which includes an interface very similar or identical to the superalloy base, and a transition layer that is gradient in oxygen concentration, where gradient means that the oxygen content increases from the interface toward the barrier layer, which is an oxidized superalloy according to this embodiment.

[0048] The substrates and targets were produced from powders with the chemical composition listed in the second column of Table 1. This composition corresponds to the specifications of the superalloy PWA1483. However, the substrates and targets were produced by spark plasma sintering at about 1200 °C and 30 MPa (PLANSEE Composite Materials GmbH). This material may therefore differ from the industrially used bulk material produced by melting and casting. In this respect it is important to note that: The average grain size of the structure is less than 50 μm, preferably less than 20 μm. Powder metallurgy production preferably starts with alloy powders rather than a mixture of elemental powders. -This allows the synthesis of the phases to occur during the production of the powder rather than through the SPS process. -Such produced targets have no texture, i.e. they are characterized by random grain orientation (e.g. measured by EBSD), which is significantly different from targets produced by melt metallurgy. The porosity of the structures produced by the SPS process is controlled to less than 10%, or preferably less than 5%. The SPS process is carried out in the temperature range of 1000-1350°C, preferably in the temperature range of 1100-1300°C, without the formation of a liquid phase.

[0049] Considering this, this material is further named superalloy substrate (SA-S) when used as a substrate and superalloy target (SA-T) when used as an evaporation target. Small disks (φ60mm) were produced from this material and machined to size (30mm×10mm×5mm) to give SA-S. Using the same process, SA-T disks (φ150mm) were produced.

[0050] Table 2 shows the main process parameters utilized for cathodic arc evaporation using SA-T as cathode in the examples described below. Prior to deposition, the process chamber was evacuated to less than 0.02 Pa and standard heating and etching steps were performed to ensure sufficient coating adhesion to the substrate. A net deposition time of 45 min was chosen for the non-reactive process (metal vapor only) and extended to 240 min for the reactive process in oxygen. This is attributed to the reduced evaporation rate of SA-T in pure oxygen reactive gas, resulting in coating thicknesses of 1.5 μm (reactive) and 2.2 μm (non-reactive), respectively. The cathode was operated at a DC arc current of 140 A with a gas flow of metal vapor only or 800 sccm oxygen (reactive process) using an INNOVA batch-type manufacturing system from Oerlikon Surface Solutions AG. SA-S and sapphire substrates were coated at a substrate temperature of about 550 °C. Only one arc source was used for deposition. A symmetric bipolar bias voltage of 40 V with a frequency of 25 kHz and a negative pulse length of 36 μsec and a positive pulse length of 4 μsec was applied to the substrate during the oxygen treatment.

[0051] The target surfaces were analyzed with a LEO 1530 scanning electron microscope (SEM). The chemical compositions of SA-T and SA-S were measured by energy dispersive X-ray spectroscopy (EDX) in the SEM.

[0052] XRD measurements of polished slices of polycrystalline target materials were carried out on a Bruker D8 Davinci diffractometer equipped with a Goebel mirror to generate a collimated beam and a LynxEye 1D detector using Cu-Kα radiation. Measurements were performed in 2θ / ω mode from 5 to 140°. For phase analysis, the Bruker software Diffrac.Eva V4.1 was used in combination with the Crystal Open Database (COD), an open access collection of crystal structures published in the Journal of Applied Crystallography 42 (2009) 726-729.

[0053] Conventional electron backscatter diffraction (EBSD) analysis was performed on the SA-T surface with a Tescan dual FIB FEG-SEM Lyra3 using a Digiview IV EDAX camera. An accelerating voltage of 20 kV and an emission current of 5 nA were used. In addition, transmission EBSD or Transmission Kikuchi Diffraction diffraction (TKD) was performed on lift-out specimens of approximately 100 nm thickness mounted on a holder with a pretilt angle of 20° relative to the pole piece at a working distance of 3 mm. Beam conditions were 30 kV and 5 nA. Chemical segregation was analyzed by ion channeling contrast imaging performed using Ga ions at 30 kV and 1.5 pA. The lift-out lamellae were finally analyzed with a JEOL JEM 2200fs transmission electron microscope (TEM) equipped with an EDAX EDS system.

[0054] Analysis of unused targets (cathode) The chemical composition of the SA-T produced by spark plasma sintering was investigated by EDX. Quantitative analysis is difficult due to the large number of elements to be analyzed and their different sensitivity to this method. However, the similarity of the materials allows a qualitative comparison (except for C). Table 1 presents the results for the virgin surface of the produced targets, with the values ​​for the composition of all elements in the third column and the values ​​of the difference (Δ) with respect to the powder composition in the fourth column. There is a good agreement in composition with the original powder, with the exception of carbon and tantalum. The crystal structure of the virgin target surface, obtained by XRD analysis, was compared with the target surface after arc operation in a non-reactive process. The 2θ / ω scan is shown in Figure 2. The XRD pattern of the virgin target (dotted line) shows several main peaks that can be indexed as fcc cubic (Fm-3m) with a = 3.59 Å. The diffraction patterns observed for the various elements constituting the superalloy (Table 1) are consistent with this cubic lattice. In addition to the individual elements, Cr2Ni3, Al 2.6 Ni 10.7 Ta 0.7 , Ni 0.9 Ta 0.1 , Ni 17 W3, Co 0.87 W 0.13 , Ni 3.28 Ti 0.72 , Ni 0.85 W 0.15or CrNi and can be considered as potential candidates for the observed fcc phase. Peaks with intensity less than 1% are also found in the XRD pattern of the virgin target surface. They may belong to the XRD pattern of tantalum oxide phases formed as a result of surface oxidation. The peaks of the XRD pattern revealed for the engineered target (solid line) a similar fcc cubic (Fm-3m) phase as observed for the virgin target surface. However, the peaks of the engineered target are slightly shifted towards higher angles, indicating a decrease in the unit cell parameter a from 3.59 Å for the virgin target to 3.58 Å for the engineered target. At the same time, the peaks of the engineered target are narrower than those of the virgin target, which may be due to a recrystallization process at the target surface and, consequently, the formation of larger crystals. The assumption of the presence of different intermetallic compounds from the X-ray diffraction analysis is in agreement with the results of the TEM measurements. It has been confirmed that these superalloy materials are indeed composed of different intermetallic compounds (see below).

[0055] A micrograph of the SA-T surface obtained from SEM with backscattered electrons using a beam voltage of 20 kV is shown in Figure 3a. The contrast in the backscattered image is mainly due to the grain orientation. This is verified by the corresponding EBSD crystal orientation map of the investigated surface, shown in a black and white (bw) version in Figure 3b. EBSD analysis reveals 88% high angle and 12% low angle grain boundaries and 7% Σ3 twin (60° at (111)) grain boundaries, with an average grain size of (5.9 ± 3.1) μm. The white dots observed in the backscattered image in Figure 3a were identified by TEM as titanium and tantalum rich precipitates. Enlarged cross sections of the different grains are shown in bright-field and dark-field scanning transmission electron microscope images in Figure 4a and Figure 4b, respectively. An EDX mapping of this detail is shown in Figure 5. This mapping shows that Cr (Figure 5b below), Co (Figure 5c) and Mo (Figure 5g) are also segregated together within the grains. The same is true for Ni (Fig. 5a), Al (Fig. 5h), Ti (Fig. 5e), and Ta (Fig. 5d). Furthermore, the mapping suggests that the precipitates consist mainly of Ta and Ti.

[0056] As mentioned before, XRD patterns obtained from the surfaces of the as-fabricated and engineered targets can be indexed with fcc phases, which could be candidates for different intermetallic compounds (Figure 2). This assumption is supported by STEM investigations, where chemical segregation was observed within and between the grains. Figure 6 shows examples of bright field (6a) and dark field (6b) micrographs of a transition across two grain boundaries. The arrow in Figure 6a indicates the location where the EDX line scan shown in Figure 6c was performed. The qualitative distribution of only the dominant elements is plotted, which varies significantly between the two grains studied. Ni / Al and Co / Cr segregation is observed, in good agreement with the mapping shown in Figure 5. This is the case for many similar line scans, indicating the presence of multiple fcc phases with very similar lattice constants.

[0057] Analysis of the targets indicates that the spark plasma sintering process produces target materials having polycrystalline structures with near random grain orientation. Additionally, analysis demonstrates the presence of different intermetallic phases with similar lattice constants, as well as the presence of precipitates in the produced materials.

[0058] Analysis of manipulated targets In the next step, the as-produced target was utilized as cathode and evaporated by arc. The evaporation was carried out under the conditions listed in Table 2. In the non-reactive process, no additional gas was used during the evaporation. This approach foregoes the possibility of reducing the inclusion of droplets in the deposited coating due to multiple scattering with gas atoms, but allows to maintain a higher degree of ionization and higher kinetic energy of the metal vapor that favors the condensation of the coating at higher energies. The reactive process was carried out with oxygen only. The value of the oxygen flow was chosen to ensure a ratio of oxygen to evaporated metal atoms of about 4-5, so as to produce IF-2 (oxidized superalloy layer), which results in almost complete oxidation of the coating. The chemical composition of the target after non-reactive process A and reactive process B was measured by EDX and is shown in Table 1 together with the difference (Δ) with respect to the original powder composition (columns 5-8). The analysis of the target surface shows a slight decrease of Al and Cr from the non-reactive to the reactive process, but no significant change in the composition of the other target elements. The XRD pattern of the target surface after arc operation in non-reactive mode is shown in Figure 2 (solid line). Compared to the virgin target (dotted line), the peaks of the engineered target are narrower and shifted towards higher angles. The peaks can also be assigned to an fcc cubic phase (Fm-3m). The average unit cell of the engineered target is slightly smaller, the lattice constant decreases from 3.584 Å (before engineering) to 3.568 Å (after engineering), and the decrease in full width at half maximum (FWHM) indicates a recrystallization process on the target surface.

[0059] Coating Synthesis Using the parameters of process A shown in Table 2, it was investigated whether coatings could be synthesized by a non-reactive process and the target chemical composition could also be maintained in the coating. The compositions obtained by EDX are shown in Table 3, in both cases coating A has the composition of the interface layer (IF-1). Except for C, where EDX was not sensitive and accurate enough, the analysis shows that only the Al concentration is decreased in the coating, and to a certain extent the Ti concentration. An initial XRD analysis of the coatings on SA-S substrates was carried out. Since the lattice constants of the coatings and SA-S are very similar, it was not possible to unambiguously assign the observed Bragg reflections to the coatings. Therefore, the measurements were repeated for the coatings on sapphire substrates (Figure 7).

[0060] The first of the two observed phases, denoted as M-1 (black line, left of the peak) with a = 3.60 Å, is almost identical to the phase of uncoated SA-S (a = 3.59 Å) (Figure 7). The reflection of the second phase, M-2 (gray line, right of the peak), is shifted towards higher 2θ angles (a = 3.56 Å). This indicates a slightly different nucleation behavior on the sapphire substrate. The lattice constant of the M-2 phase was measured to be about 3.56 Å. TEM investigation of the target (and substrate) material already showed several intermetallic phases, and EDX mapping showed that in addition to precipitates that segregate together, at least two element groups are present. These two groups may condense at different temperatures, resulting in this phase separation.

[0061] In additional experiments, the complete stack of layers was investigated according to process B. After the initial pretreatment of SA-S described above, IF-1 was formed by arc evaporation in non-reactive mode with no additional interfaces in SA-S with a thickness of about 500 nm. In a subsequent step, 800 sccm of oxygen was supplied to the arc evaporation process and a short transition from non-reactive to reactive mode was performed. Together with a double rotation of the substrate, this results in the formation of a multi-layer structure and ultimately the nucleation of an oxide coating of about 1.5 μm. A STEM bright field image of the complete layer stack is shown in Figure 8a. The interface between the substrate and the interface layer IF-1 is shown by a dashed line in Figures 8b and 8c. This interface is investigated in more detail by the TKD in Figure 8c and the corresponding image quality map in Figure 8b, here in black and white. The orientation mapping showed epitaxial growth on the grains in the IF-1 region followed by the nucleation of numerous very small grains of arbitrary orientation and the growth of larger grains that eventually nucleate on the finer grains in this transition region and form the oxide region of the layer stack. A high-resolution (HR)-TEM micrograph of a magnified area of ​​the interface is shown in Figure 9. The micrograph shows that the lattice planes of the ST-A and coating are parallel with the same distance between the planes, again confirming the epitaxial growth of the coating on the substrate.

[0062] Thereby, the possibility of producing a complete layer stack for a bond coat by cathodic arc evaporation in an in situ process sequence, i.e. without breaking the vacuum, is detailed. It was demonstrated that targets from powders with almost identical chemical composition to the superalloy substrate can be produced and used as cathodes for arc evaporation. The targets can be operated in non-reactive and reactive deposition processes. Examination of the target surface after treatment with and without oxygen reactive gas revealed little effect on the chemical composition and crystal structure. Coatings synthesized in non-reactive deposition mode are also similar in chemical composition and crystal structure with respect to the target. The approach to forming a complete layer stack for a bond coat in one process allows the design principle of grading the profile by controlled addition of reactive oxygen gas or by operation of additional targets of the same or different elemental composition. Furthermore, epitaxial growth was observed on the grains of the polycrystalline substrate at the substrate interface. The addition of oxygen to the running arc evaporation process leads to the formation of a fine grain transition zone, which finally leads to the nucleation of larger crystals in the fully oxidized areas of the layer stack. The presented approach has the potential to realize epitaxial growth on any superalloy material and to implement gradients to coatings with different chemical compositions and functionalities.

[0063] [Table 1]

[0064] [Table 2]

[0065] [Table 3]

Claims

1. - providing a superalloy (SA) substrate to a PVD coating unit; - providing a superalloy target as the cathode of the arc source of said coating unit, said target having essentially the same composition as the superalloy constituting said substrate; - applying a substrate bias to the substrate; - depositing an interface layer (IF-1) of superalloy on the surface of said substrate by vacuum arc evaporation from said superalloy target; - providing a reactive gas supply comprising oxygen to said coating unit; - depositing by vacuum arc deposition a transition layer (TL) of a superalloy or of a different metal composition having essentially the same composition as the superalloy constituting said substrate, in which the oxygen content of said transition layer (TL) is increased from said interface layer (IF-1) by varying the partial pressure of said reactive gas feed in the process atmosphere; - depositing, by vacuum arc deposition in a process atmosphere containing a higher concentration of the reactive gas feed, subsequent to the deposition of the transition layer (TL), a barrier layer (IF-2) comprising an oxide of the superalloy having essentially the same composition or an oxide of the different metal composition in a larger amount than in the transition layer (TL); Including, the interface layer (IF-1) is deposited with a crystal structure that is compatible with the crystal structure of the superalloy (SA) substrate; The different metal composition differs from the superalloy having essentially the same composition in at least the concentration or addition of at least one of the following additional elements: Mg, Al, Cr, Er, Y, Zr, La, Hf, Si; The superalloy (SA) substrate is a Co-based superalloy substrate and the superalloy target is a Co-based superalloy target; or The method of coating, wherein the superalloy (SA) substrate is a Ni-based superalloy substrate and the superalloy target is a Ni-based superalloy target.

2. A coating method as described in claim 1, characterized in providing at least one further target having a further metal composition for depositing the transition layer (TL) of the different metal composition and / or the barrier layer (IF-2) of an oxide of the different metal composition.

3. A coating method as described in claim 1 or 2, characterized in that a gaseous precursor is provided in parallel with vacuum arc evaporation of the superalloy target to deposit the transition layer (TL) of the different metal composition and / or the barrier layer (IF-2) of an oxide of the different metal composition.

4. Coating method according to any one of claims 1 to 3, characterized in that the oxide of the superalloy having essentially the same composition of the barrier layer (IF-2) and / or the oxide of the different metal composition are deposited with a ratio of oxygen atoms to metal atoms of at least 1.5, or even at least 5, to form thermodynamically stable oxides from the superalloy metal and / or the different metal composition evaporated during the deposition of the barrier layer (IF-2).

5. 5. Coating method according to any one of claims 1 to 4, characterized in that the interface layer (IF-1) is deposited with pure metal vapor without process gas.

6. 6. A method of coating according to any one of claims 1 to 5, characterized in that an inert gas supply is provided to the coating unit to deposit at least one of the interface layer (IF-1), the transition layer (TL) and the barrier layer (IF-2) in an inert gas containing process atmosphere.

7. 7. The method according to claim 1, wherein the superalloy target is produced by a powder metallurgy process.

8. A coating method according to any one of claims 1 to 7, characterised in that in a further process step a ceramic top layer is applied to the surface of the barrier layer (IF-2).

9. 9. The method of claim 8, wherein the ceramic top layer is applied by a thermal spray technique.

10. - a superalloy (SA) substrate, - an interface layer (IF-1) directly on the surface of said superalloy (SA) substrate, of essentially the same superalloy composition as the superalloy constituting said substrate, followed by a transition layer (TL) of essentially the same superalloy and an oxide of said superalloy or a different metal composition and an oxide of said different metal composition, the oxygen content of said transition layer increasing from said interface layer (IF-1); a barrier layer (IF-2) of oxide of said essentially same superalloy or of said different metal composition; Including, the interface layer (IF-1) has a crystal structure that is matched to the crystal structure of the surface of the superalloy (SA) substrate; The different metal composition differs from the essentially same superalloy composition in at least the concentration or addition of at least one of the following additional elements: Mg, Al, Cr, Er, Y, Zr, La, Hf, Si; The superalloy workpiece, wherein the superalloy (SA) substrate is a Co-based superalloy substrate or a Ni-based superalloy substrate.

11. The workpiece according to claim 10, characterized in that the oxygen content of the transition layer (TL) increases stepwise or gradually from the interface layer (IF-1) to the barrier layer (IF-2).

12. 12. The workpiece of claim 10 or 11, wherein the different metal composition differs from the essentially same superalloy composition by at least one additional element.

13. 13. The workpiece of claim 12, wherein the at least one additional element has an electronegativity of 1.4 or less.

14. 14. The workpiece of claim 12 or 13, wherein the at least one further element comprises at least one of the lanthanides.

15. 15. The workpiece according to any one of claims 10 to 14, characterized in that at least a part of the further element is oxidized and deposited within the grains as a solid solution (SS) and / or along the grain boundaries of the transition layer (TL) and / or the barrier layer (IF-2) as a dispersion strengthened oxide (ODS).

16. 16. The workpiece according to claim 10, wherein the concentration of at least one of a metal element or silicon in the transition layer (TL) increases stepwise or gradually from the interface layer (IF-1) to the barrier layer (IF-2).

17. The oxides of different metal compositions are selected from the group consisting of: Aluminum oxide, aluminum-chromium oxide, erbium oxide, yttrium oxide, yttrium-aluminum oxide, magnesium-aluminum oxide, aluminum-silicon oxide, hafnium-silicon oxide 17. The workpiece according to claim 10, characterized in that it comprises at least one of the following or a mixture thereof:

18. The workpiece of claim 17, wherein the aluminum oxide or aluminum-chromium oxide is Al 2 O 3 or (AlCr) 2 O 3 having a corundum crystal structure, and the erbium oxide or yttrium oxide is Er 2 O 3 or Y 2 O 3 having a cubic crystal structure.

19. 20. The workpiece of claim 18, wherein greater than 55% of each crystal structure is corundum or cubic structure.

20. The workpiece of claim 10, wherein the oxides of different metal compositions include an aluminum-containing oxide.

21. The workpiece of claim 10, wherein the oxides of different metal compositions include a chromium-containing oxide.

22. 22. The workpiece according to any one of claims 10 to 21, comprising a ceramic top layer on a surface of the barrier layer (IF-2).

23. A method for manufacturing a superalloy (SA) workpiece comprising the coating method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Component, apparatus and method for manufacture of layer system

    JP2007217795A

  • Ceramics-coated member, and its production method

    JP2008202092A

  • Hard film-coated tool and method of manufacturing the same

    JP2011224768A

  • Surface-coated cutting tool excellent in wear-resistance

    JP2016036873A